2016
DOI: 10.1177/1524839916647331
|View full text |Cite
|
Sign up to set email alerts
|

Process Evaluation of Making HEPA Policy Practice

Abstract: This study examines the link between implementation of Strategies to Enhance Practice (STEPs) and outcomes. Twenty after-school programs (ASPs) participated in an intervention to increase children's accumulation of 30 minutes/day of moderate to vigorous physical activity (MVPA) and quality of snacks served during program time. Outcomes were measured via accelerometer (MVPA) and direct observation (snacks). STEPs implementation data were collected via document review and direct observation. Based on implementat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 39 publications
3
13
0
Order By: Relevance
“…As detailed in the process evaluation, [39, 40] during spring 2015 (the only year of intervention for the delayed group) 9 of the 10 delayed ASPs reduced their schedule PA opportunities to no more than 60 minutes/day and 5 of them allowed children to select a sedentary activity, such as using the computer lab, during this time. Two recent study show that extending the time allocated for PA [53] and not allowing children to select an inactive activity [54] were associated with higher levels of MVPA and less time spent sedentary in ASPs.…”
Section: Discussionmentioning
confidence: 99%
“…As detailed in the process evaluation, [39, 40] during spring 2015 (the only year of intervention for the delayed group) 9 of the 10 delayed ASPs reduced their schedule PA opportunities to no more than 60 minutes/day and 5 of them allowed children to select a sedentary activity, such as using the computer lab, during this time. Two recent study show that extending the time allocated for PA [53] and not allowing children to select an inactive activity [54] were associated with higher levels of MVPA and less time spent sedentary in ASPs.…”
Section: Discussionmentioning
confidence: 99%
“…Teachers were determined to be in the high group if their index score for that strategy was above the median index score across teachers. Index scores were created by summing baseline, outcome, and change from baseline to outcome in the percentage of time a strategy was observed during PE lessons (Weaver, Moore, et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…Similar results have been documented in structured, staff-led after-school programs, with many programs failing to provide fruits, vegetables, and water on a regular basis and demonstrating challenges meeting PA guidelines [ 16 , 27 ]. Studies of health policy implementation in staff-led OST programs have revealed improved nutrition and PA outcomes, suggesting volunteer-led OST programs could also benefit from such interventions [ 28 , 29 ]. Yet to date, interventions to promote nutrition and PA guidelines to volunteer-led OST programs have not been undertaken.…”
Section: Discussionmentioning
confidence: 99%